If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Cosx = cotx(secx) Multiply cotx * cesx osxC = c2eostx2 Solving osxC = c2eostx2 Solving for variable 'o'. Move all terms containing o to the left, all other terms to the right. Add '-1c2eostx2' to each side of the equation. -1c2eostx2 + osxC = c2eostx2 + -1c2eostx2 Combine like terms: c2eostx2 + -1c2eostx2 = 0 -1c2eostx2 + osxC = 0 Factor out the Greatest Common Factor (GCF), 'osx'. osx(-1c2etx + C) = 0Subproblem 1
Set the factor 'osx' equal to zero and attempt to solve: Simplifying osx = 0 Solving osx = 0 Move all terms containing o to the left, all other terms to the right. Simplifying osx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-1c2etx + C)' equal to zero and attempt to solve: Simplifying -1c2etx + C = 0 Reorder the terms: C + -1c2etx = 0 Solving C + -1c2etx = 0 Move all terms containing o to the left, all other terms to the right. Add '-1C' to each side of the equation. C + -1C + -1c2etx = 0 + -1C Combine like terms: C + -1C = 0 0 + -1c2etx = 0 + -1C -1c2etx = 0 + -1C Remove the zero: -1c2etx = -1C Add 'c2etx' to each side of the equation. -1c2etx + c2etx = -1C + c2etx Combine like terms: -1c2etx + c2etx = 0 0 = -1C + c2etx Simplifying 0 = -1C + c2etx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x^7=0.01 | | Cosx=cotx(sinx) | | Cosx=cotx(y) | | -8y+5=-67 | | 8/2=-a/9 | | 1+x/6=-3 | | 9x-20+9x-48=58 | | (2x+3)(6x+32)= | | 5x+75+2x-21=180 | | -8+b=12 | | 10-4x=-2x | | -2-p=-13 | | 6.7=0.2x+4.5 | | 62+12m=-10 | | A-7=6 | | 3a/2=2/3 | | 31/2=2/3 | | 3x+x+(80+x)=455 | | (5-w)(5w-4)=0 | | .9-.135= | | 15y+7= | | B+15=10 | | 7(3y-2)-6y= | | 4x-5+9x+37=110 | | x^5z^4/xz^3 | | e^1/2x=2 | | 3x^4-2x^2+(-6x^5)-7x=0 | | 2x*2+4x=0 | | 4=35-X | | -6-2+(-5)=0 | | X-3+1=5x-4x+1 | | 7b-80=4 |